Chloral Hydrate Sedation in a Dexmedetomidine Era. (August 2020) - Farr, Kimberley M.; Moffett, Brady S.; Jones, Jennifer L.; Rogers, Amber P.; Chumpitazi, Corrie E.
Brief Overview: The use of chloral hydrate as the primary sedation agent has declined across the nation after commercial production of the liquid formulation ceased. Although alternative sedatives have gained popularity, some pharmacies have continued to provide oral chloral hydrate by compounding it from raw ingredients. Thus, oral chloral hydrate use has continued in children despite the availability of alternative effective agents.Objective: The purpose of this investigation was to evaluate institutional chloral hydrate utilization as the primary agent for procedural sedation.Design/Methods: We conducted a retrospective study of patients given chloral hydrate for procedural sedation from October 2010 to December 2016. The hospital pharmacy database of chloral hydrate use at our 2 free-standing children's hospitals was reviewed and matched to procedure billing data.Results: There were 5874 chloral hydrate administrations for procedural sedation during the study period. The highest rates of use occurred in 2014, when there were 1420 chloral hydrate orders within our hospital. The large majority of sedations were for cardiac studies/procedures (n = 4250, 72.4%).Conclusions: Despite significant declines in use of chloral hydrate for procedural sedation across the country, local utilization of oral chloral hydrate remains high. Recent declines may be due to high-use clinical sites transitioning to alternative sedatives such as intranasal dexmedetomidine.